The strategic management process at the public planning unit level - Montanari, John R.; Bracker, Jeffrey S. (Strategic Management Journal, 1986)
Abstract This paper describes a normative strategic management process for the public sector. It focuses on the state agency or department as the strategic public planning unit (SPPU). Each department within a state Government provides a distinctly different service to a more or less homogeneous segment of the state's citizenry. Therefore, for strategic management purposes, each state unit operates in its unique context and must meet the demands of varied constituency publics if it is to be a viable and effective provider of its service. The process herein described recognizes the unique aspects of public sector strategic management and integrates several stages that are specific to the public sector into an established private sector strategic management framework.